The Use of Transcription Terminators to Generate Transgenic Lines of Chinese Hamster Ovary Cells (CHO) with Stable and High Level of Reporter Gene Expression - Gasanov, N. B. (Acta Naturae, 2015)
Mammalian cell lines are widely used to produce recombinant proteins. Stable transgenic cell lines usually contain many insertions of the expression vector in one genomic region. Transcription through transgene can be one of the reasons for target gene repression after prolonged cultivation of cell lines. In the present work, we used the known transcription terminators from the SV40 virus, as well as the human β- and γ-globin genes, to prevent transcription through transgene. The transcription terminators were shown to increase and stabilize the expression of the EGFP reporter gene in transgenic lines of Chinese hamster ovary (CHO) cells. Hence, transcription terminators can be used to create stable mammalian cells with a high and stable level of recombinant protein production.